Improving Teachers Capabilities In Using The School Environment As A Learning Source Through Discussion Of Teacher Work Group (Kkg) At Sd Negeri 004 Kecamatan Pendalian Iv Koto - Ernis Susanti (STKIP Rokania Pasir Pangaraian, 2021)
One of the appropriate learning strategies for this is learning with the Pakem approach. By utilizing the school environment as a learning resource, the implementation of standard learning will enable students to develop creativity, motivation and participation in learning. From the observations of prospective researchers as school supervisors, so far the teachers at SD Negeri 004 Pendalian IV Koto, very rarely and never even use the school environment as a source of learning. The implementation of this research begins with data collection using an observation format, learning scenario assessment instruments and learning implementation assessment instruments. Furthermore, the data that has been collected is analyzed using descriptive analysis, the result is that in the first cycle the average value obtained from the attitude of the teacher in discussing the discussion is 79.38 in the